Necessidades de cuidado de mulheres em climatério com hipertensão: possibilidades de atuação do enfermeiro - Castilhos, Lara (2020)
This research aims to understand the care needs of women in climacteric with Systemic Arterial Hypertension attached to the Family Health Strategy of a city in the state of Rio Grande do Sul. Method: this is a quantitative and qualitative study , carried out in a city in the interior of the state of Rio Grande do Sul. The study participants, in the quantitative stage, were 42 women who previously participated in the matrix project. Of these, 15 women participated in the qualitative stage. The inclusion criteria were: women between 40 and 65 years old, diagnosed with hypertension, linked to the Family Health Units. Data collection took place through semi-structured interviews. The quantitative results were analyzed using the matrix project database and the qualitative results with participatory analysis, based on hermeneutics-dialectics. The interviews were transformed into narratives and returned to the participants. Based on that, the argument centers were identified. Results: the data revealed that 57.14% (n = 24) of the women had up to eight years of study, 47.61% (n = 20) were employed or self-employed, 52.38% (n = 22) were legally married , 35.71% (n = 15) received up to two minimum wages. 42% (n = 26) are Catholic. 83.33% (n = 35) of women do not use alcohol and cigarettes. 83.33% (n = 35) women have obesity. 73.81% (n = 31) did not report Diabetes Mellitus and 80.96% (n = 34) did not have peripheral vascular disease in the family. The participants' care needs include handling the changes from the climacteric, such as: hot flushes, skin changes, sweating, forgetfulness, decreased libido, weight gain and mood changes. Also about the use of medication for hypertension and ways of taking care of food. They refer to seek medical attention, friends, family or internet, when they need more information about the climacteric and hypertension. There is a need for nurses to strengthen bonding relationships with women in climacteric with hypertension, in order to become a reference in care practices. Final considerations: it is recommended, as possibilities for nurses to work with women, to carry out health groups, home visits and nursing consultations. Therefore, women must be cared for in an integral and singular way, breaking with the fragmentation of care.